Hubungan Antara Budaya Organisasi Dengan Kepuasan Kerja Pada Pegawai Rsud Dr. Sayidiman Magetan - Amada Dhona, Arwin, Achmad Dwityanto, S.Psi, M.Si (2016)
The aim of this research is to know correlation between organization culture with job satisfication in employee's RSUD dr. Sayidiman Magetan. Hypothesis advanced by which is there are a positive relationship between culture with satisfaction organization work in the hospital employees dr. Sayidiman Magetan. Technique the sample used in this research is by using technique purposive sampling, with the subject of as many as 144 employees that may be analyzed 85 employees. Using a technique the sample collection purposive sampling. A method of the data using scale organization culture and scale of job satisfaction. Data analysis technique using correlation test product moment. Data analysis to research it uses SPSS 19.0, obtained value a correlation coefficient of 0,644 with significance (p) = 0,000; (p ≤ 0.01) mean there are a positive correlation very significant between organization culture with job satisfaction. Contributions Effective (CE) of both variables indicated by the value of (r²) = 0,415 which means that the variable organization cultural at work against job satisfaction of 41.5 % and 58.5 % the rest influenced by factors other than variable cultural organization. The organization culture high with Empirical Averages (EA) of 109,96 and Hypothetic Averages (HA) of 95. While category job satisfaction high with Empirical Averages (EA) of 138,27 and Hypothetic Averages (HA) of 117,5. Keywords: organization culture, job satisfication